Optimizing Public Services through Industrial Work Practice Management Applications Using Extreme Programming Methods - Azis, Muh Nur Luthfi; Hapsari, Ayunda Nur (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Industrial work practice or industrial Internship is applying knowledge and skills to solve real problems. It becomes one of the efforts to improve the quality of human resources in an agency or company. Managing the industrial Internship at PT Artha Abadi is still being carried out using physical documents. This allows errors to occur in recording Industrial Internship data and documents. This study aimed to overcome existing problems so that the management of Industrial Internship activities at PT Artha Abadi is more systematic, organized and efficient. The method used in creating this system is the Extreme Programming method which aims to increase effectiveness and efficiency in the software development process. The Industrial Internship Management Application is built using the Laravel framework and MySQL as its database. The tools used to create this system are XAMPP as a database server and Visual Studio Code for a text editor, in system testing using Black Box Testing to test the software's functionality. Testing shows that the Industrial Internship Management Application does not experience system errors or bugs. The results of this study show that the application is built according to the main objectives and is ready to be implemented so that the Industrial Internship at PT Artha Abadi runs more systematically, organized, and efficiently.